Composite permanent magnet material and preparation method and application thereof
By mixing rare earth permanent magnet powder after acid reagent treatment and heat treatment with coupling agent and copolymer, combined with the composite process of binder, a composite permanent magnet material with excellent magnetic properties and mechanical strength was prepared, and the SmFeN-based material was solved The problem of large shrinkage rate at high temperatures.
Patent Information
- Application Number
- CN202411735135.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
AI Technical Summary
SmFeN-based composite permanent magnet materials have a high shrinkage rate when used at high temperatures, which leads to the product being easily deformed, especially in magnetic ring products. Long-term use of high temperatures will cause the shell to fall off.
By reacting rare earth permanent magnet powder with acid reagent under a heat treatment process, and then mixing with coupling agent and copolymer, the particle size and morphology of the powder is optimized, and coated and modified on the surface, finally combining with the binder. The composite process of the composite permanent magnet material with excellent magnetic properties and mechanical strength was prepared.
It significantly reduces the shrinkage rate of the material when used for a long time at higher temperatures, ensures the magnetic properties and mechanical strength of the composite permanent magnet material, and is suitable for applications in high-temperature environments.
Smart Images

Figure BDA0005161289240000151 
Figure BDA0005161289240000161
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnetic materials, and in particular to a composite permanent magnetic material and a preparation method and application thereof. Background Art
[0002] As information products such as computers develop towards miniaturization, lightness and high performance, the market has put forward higher requirements for the magnetic properties of permanent magnet materials. Among various permanent magnet materials, rare earth permanent magnet materials have attracted widespread attention due to their excellent magnetic properties. Rare earth permanent magnet materials are a type of high-performance permanent magnet materials formed by rare earth elements and transition elements, including the first generation SmCo5 series, the second generation Sm2Co 17 The third generation of NdFeB rare earth permanent magnet materials. Among them, NdFeB rare earth permanent magnet materials not only have more abundant raw materials, but also have higher magnetic properties. They are also called "magnet king" in the industry and are widely used in automobiles, home appliances, office supplies, aerospace, medical equipment and instrumentation. However, with the increase in usage, the prices of key rare earth elements such as Nd, Pr, Dy and Tb have also risen.
[0003] Compared with NdFeB rare earth permanent magnet materials, samarium iron nitrogen (SmFeN) rare earth permanent magnet materials have higher Curie temperature, higher anisotropy field and similar saturation magnetization than NdFeB rare earth permanent magnet materials, and may become a new generation of rare earth permanent magnet materials. However, since the main magnetic phase of SmFeN rare earth permanent magnet materials will undergo irreversible decomposition when the temperature exceeds 600°C, it is difficult to make dense magnets through traditional sintering processes. Therefore, injection molding is generally used to make bonded magnets.
[0004] Prior art CN112331472A discloses a method for preparing high-performance modified SmFeN magnetic powder, which uses an antioxidant and a coupling agent to perform surface modification on SmFeN powder, thereby significantly improving its antioxidant performance and bonding performance with a matrix. The modified SmFeN magnetic powder prepared by the method is mixed with a binder matrix for granulation and injection molding, and the resulting SmFeN permanent magnet has high magnetic properties, antioxidant properties, fluidity and mechanical properties, is easy to be injection molded, and can meet the requirements of a more demanding use environment.
[0005] However, in the preparation process of SmFeN composite permanent magnet materials, in addition to adding samarium iron nitrogen magnetic powder, a large amount of polymer binder is also added. The samarium iron nitrogen composite permanent magnet materials prepared with polymer binders also have the disadvantages of large high-temperature shrinkage and easy deformation when used at high temperatures. Especially for magnetic ring products, after working for a long time at a temperature close to 120°C, the product will shrink and fall off the casing.
[0006] Therefore, providing a permanent magnetic material with excellent magnetic properties and low shrinkage even when the material is exposed to high temperatures for a long time has become an urgent problem to be solved. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a composite permanent magnetic material and its preparation method and application. In the preparation method of the present invention, rare earth permanent magnetic powder reacts with an acid reagent under a heat treatment process, and then is sequentially mixed with a coupling agent and a copolymer, thereby optimizing the particle size and morphology of the material, improving the particle dispersibility, and realizing the coating and modification of the surface of the permanent magnetic powder. Combined with the composite process with a binder, the obtained composite permanent magnetic material not only has excellent magnetic properties and strong mechanical strength, but also effectively reduces the shrinkage rate of the material when it is at a high temperature for a long time.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a composite permanent magnetic material, the preparation method comprising the following steps:
[0010] (1) performing a first mixing of rare earth permanent magnet powder, an acid reagent and a first solvent, and then performing a heat treatment to obtain a first mixed material;
[0011] (2) performing a second mixing of the first mixed material, the coupling agent and the second solvent to obtain a second mixed material;
[0012] (3) performing a third mixing of the second mixed material and the copolymer to obtain a third mixed material;
[0013] (4) The third mixed material is mixed with a binder for a fourth time to obtain the composite permanent magnetic material.
[0014] In the preparation method provided by the present invention, an acid reagent is used to treat the rare earth permanent magnet powder. On the one hand, the particles with extremely small particle size in the rare earth permanent magnet powder can be reacted to improve the uniformity of the particle size of the rare earth permanent magnet powder, avoid the agglomeration of the permanent magnet powder with too small particle size in the subsequent operation process, and optimize the morphology and surface state of the powder, thereby improving the shrinkage rate of the obtained material. On the other hand, the acid reagent is mixed with the rare earth permanent magnet powder and combined with a heat treatment process to form a coating film on the surface of the rare earth permanent magnet powder, thereby preventing the oxidation of the rare earth permanent magnet powder in the subsequent operation process, thereby affecting the performance of the obtained material; secondly, the first mixed material obtained after the heat treatment is then coupled with the coupling agent. The first mixed material is mixed with a coupling agent to couple the first mixed material and improve the compatibility of the material with the subsequently added reactants; furthermore, the second mixed material treated with the coupling agent reacts with the copolymer to achieve organic coating of the second mixed material, further improving the effect of preventing the internal permanent magnetic powder from being oxidized, thereby improving the magnetic properties of the material; then, the third mixed material obtained after the reaction with the copolymer reacts with the binder again, during which the copolymer on the third mixed material and the binder will undergo a polymerization reaction, adjust the molecular structure of the binder, achieve a special composite of the rare earth permanent magnetic powder and the binder, and successfully prepare a composite permanent magnetic material with excellent magnetic properties, high mechanical strength and low shrinkage.
[0015] In the preparation method of the present invention, rare earth permanent magnet powder reacts with an acid reagent under a heat treatment process and is then sequentially mixed with a coupling agent and a copolymer, thereby optimizing the particle size and morphology of the rare earth permanent magnet powder, improving the particle dispersibility, and coating and modifying the surface of the permanent magnet powder. Then, the composite process with a binder is combined, so that the obtained composite permanent magnet material not only has excellent magnetic properties and strong mechanical strength, but also effectively reduces the shrinkage rate of the material when it is exposed to a high temperature for a long time.
[0016] Preferably, the rare earth permanent magnet powder in step (1) comprises samarium iron nitrogen magnetic powder.
[0017] Preferably, the particle size D50 of the rare earth permanent magnet powder in step (1) is 1.8-2.5 μm, for example, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm or 2.5 μm, etc.
[0018] The present invention regulates the particle size D50 of the rare earth permanent magnet powder reacting with the acid reagent, and can have a good powder particle size distribution and powder surface state, which is conducive to the composite permanent magnet material obtained in the subsequent process having excellent magnetic properties, high mechanical strength and low shrinkage rate change; if the particle size D50 of the rare earth permanent magnet powder used is too small, the mechanical strength of the final material will be deteriorated and the shrinkage rate at a higher temperature will be increased; if the particle size D50 of the rare earth permanent magnet powder is too large, the mechanical strength and magnetic properties of the composite permanent magnet material obtained will be reduced.
[0019] Preferably, the rare earth permanent magnet powder in step (1) is prepared by ball milling and then vibration milling of rare earth permanent magnet coarse material.
[0020] The invention crushes rare earth permanent magnet powder into suitable size through ball milling and vibration milling processes, thereby effectively reducing the shrinkage rate of the obtained composite permanent magnet material.
[0021] Preferably, the average particle size of the rare earth permanent magnet coarse material is 15-25 μm, for example, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm.
[0022] Preferably, the particle size D50 of the material obtained after the ball milling is 3-3.5 μm, for example, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm or 3.5 μm.
[0023] Preferably, the ball milling aid includes ethanol.
[0024] Preferably, the ball-milled material is dried and then vibrated.
[0025] Preferably, the drying is performed under the protection of a nitrogen atmosphere and / or an inert atmosphere.
[0026] Preferably, the drying temperature is 110-120°C, such as 110°C, 112°C, 114°C, 116°C, 118°C or 120°C.
[0027] Preferably, the acid reagent in step (1) comprises phosphoric acid.
[0028] In the present invention, phosphoric acid is used as an acid reagent. On the one hand, the particles with smaller particle sizes in the rare earth permanent magnet powder after crushing can be effectively reacted, the uniformity of the particle size of the rare earth permanent magnet powder can be improved, and the morphology and surface state of the powder can be optimized. On the other hand, the addition of phosphoric acid combined with the subsequent heat treatment process can form a phosphating film on the surface of the rare earth permanent magnet powder, the rare earth permanent magnet powder is coated, and the anti-oxidation effect of the permanent magnet powder is better improved, so that the magnetic properties of the obtained composite permanent magnet material can be improved and the shrinkage rate can be reduced.
[0029] Preferably, in step (1), the amount of the acid reagent added is 0.5-2 wt % of the mass of the rare earth permanent magnet powder.
[0030] In the present invention, if the amount of the acid reagent added is too low, it is impossible to effectively remove particles with smaller particle sizes in the rare earth permanent magnet powder and to achieve effective optimization of the particle morphology, the uniformity of the particle size is poor, and there are many material morphologies with sharp surfaces, thereby affecting the shrinkage rate of the obtained composite permanent magnet material. In addition, a small amount of the acid reagent added will also lead to a poor coating effect on the particles, and the particles are prone to oxidation during subsequent operations, thereby affecting the magnetic properties of the final composite permanent magnet material. If the amount of the acid reagent added is too high, it will cause the composite permanent magnet powder to be excessively dissolved, the non-magnetic phase in the composite permanent magnet material will increase, and the magnetic properties of the composite permanent magnet material will be reduced.
[0031] Optionally, the concentration of the acid reagent in step (1) is 75-85wt%, for example, 75wt%, 76wt%, 77wt%, 78wt%, 79wt%, 80wt%, 81wt%, 82wt%, 83wt%, 84wt% or 85wt%, etc.
[0032] Preferably, in step (1), the mass ratio of the rare earth permanent magnet powder to the first solvent is 1:(1-2), for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2, etc.
[0033] Preferably, the specific process of the first mixing in step (1) includes: mixing the rare earth permanent magnet powder with a first solvent to form a mixed slurry, and then mixing the mixed slurry with the acid reagent.
[0034] Preferably, after the first mixing in step (1), the mixed product obtained by the first mixing is further dried.
[0035] Preferably, the drying temperature is 120-130°C, for example, 120°C, 122°C, 124°C, 126°C, 128°C or 130°C.
[0036] Preferably, the temperature of the heat treatment in step (1) is 120-130°C, for example, 120°C, 122°C, 124°C, 126°C, 128°C or 130°C.
[0037] In the present invention, if the heat treatment temperature is too low, the protective film on the surface of the rare earth permanent magnet powder will not be dense enough, resulting in low magnetic properties of the final composite permanent magnet material; if the heat treatment temperature is too high, it will lead to increased energy consumption and affect the structure of the protective film, thereby affecting the performance of the obtained composite permanent magnet material.
[0038] Preferably, the heat treatment time in step (1) is 1-3 h, such as 1 h, 1.5 h, 2 h, 2.5 h or 3 h.
[0039] Preferably, in step (2), the coupling agent is added in an amount of 0.5-1.0 wt% of the first mixed material, such as 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt% or 1.0 wt%.
[0040] In step (2) of the present invention, if the amount of coupling agent added is too small, the compatibility of the materials cannot be improved, thereby causing the reaction effect between the materials and the subsequently added reactants to deteriorate, affecting the performance of the final composite permanent magnetic material; if the amount of coupling agent added is too large, the non-magnetic phase in the final composite permanent magnetic material will increase, thereby affecting the magnetic properties of the material.
[0041] Preferably, the coupling agent in step (2) comprises any one of a silane coupling agent, a titanate coupling agent or an aluminate coupling agent, or a combination of at least two thereof.
[0042] Preferably, in step (2), the mass ratio of the first mixture to the second solvent is 1:(0.3-0.8), for example, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7 or 1:0.8, etc.
[0043] Preferably, in step (2), the second mixed product is further dried.
[0044] Preferably, the drying temperature is 110-130°C, for example, 110°C, 112°C, 114°C, 116°C, 118°C, 120°C, 122°C, 124°C, 126°C, 128°C or 130°C, etc.
[0045] Preferably, in step (3), the amount of the copolymer added is 0.5-2.0wt% of the mass of the second mixed material, such as 0.5wt%, 0.8wt%, 1.1wt%, 1.4wt%, 1.7wt% or 2.0wt%.
[0046] In step (3) of the present invention, if the amount of copolymer added is too small, the second mixed material cannot be effectively coated, so that the rare earth permanent magnet powder inside the material is easily oxidized, affecting the magnetic properties of the obtained composite permanent magnet material. In addition, if the amount of copolymer added is too small, it will also affect the composite effect of the material and the binder, thereby increasing the shrinkage rate of the final composite permanent magnet material. If the amount of copolymer added is too large, its proportion in the composite permanent magnet material is too large, resulting in a decrease in the performance of the material.
[0047] Preferably, the copolymer in step (3) comprises ethylene butyl acrylate copolymer.
[0048] Preferably, the product after the third mixing in step (3) is further subjected to banburying to obtain the third mixed material.
[0049] In the present invention, after the material and the copolymer are reacted, a mixing process is also carried out, and the agglomerated material after the reaction can be dispersed under the action of shear force, thereby improving the complete compounding of the material organically coated by the copolymer and the binder, thereby improving the performance of the obtained composite permanent magnetic material and reducing its shrinkage rate under high temperature and long-term operation.
[0050] Preferably, the banburying is carried out in nitrogen and / or inert gas.
[0051] Preferably, the mixing temperature is 110-130°C, for example, 110°C, 112°C, 114°C, 116°C, 118°C, 120°C, 122°C, 124°C, 126°C, 128°C or 130°C, etc.
[0052] Preferably, the kneading time is 0.5-2 h, such as 0.5 h, 0.8 h, 1.1 h, 1.4 h, 1.7 h or 2 h.
[0053] Preferably, the adhesive in step (4) comprises nylon 12.
[0054] The present invention adopts specific nylon 12 as a binder, which can effectively improve the magnetic properties of the composite permanent magnetic material, enhance the mechanical strength of the material and improve the temperature resistance of the material, so that the obtained composite permanent magnetic material has excellent comprehensive performance.
[0055] Preferably, in step (4), the mass ratio of the third mixed material to the binder is (8-9.5):(0.5-2), for example, 8:2, 8.5:1.5, 9:1 or 9.5:0.5, etc.
[0056] In the present invention, if the mass ratio of the third mixed material to the binder is too low and the amount of binder added is too much, the magnetic properties of the obtained composite permanent magnet material will be affected, and the shrinkage rate of the composite permanent magnet material will increase when it is exposed to a high temperature for a long time; if the mass ratio of the two is too high and the amount of binder added is too little, the mechanical strength of the composite permanent magnet material will decrease.
[0057] Preferably, after the fourth mixing in step (4), the mixed material is further kneaded and granulated.
[0058] In a second aspect, the present invention provides a composite permanent magnetic material, which is prepared by the preparation method described in the first aspect.
[0059] The composite permanent magnetic material provided by the present invention is prepared by a specific preparation method. The obtained composite permanent magnetic material has excellent magnetic properties, strong mechanical strength, and the shrinkage rate of the material is still low when it is exposed to high temperature for a long time.
[0060] In a third aspect, the present invention provides an application of a composite permanent magnetic material, wherein the composite permanent magnetic material is applied in the fields of computers, automobiles, household products, aerospace, medical equipment or instrumentation.
[0061] The composite permanent magnetic material provided by the present invention can be applied to any application field that can be thought of by those skilled in the art.
[0062] Compared with the prior art, the present invention has at least the following beneficial effects:
[0063] (1) In the preparation method of the present invention, the rare earth permanent magnet powder reacts with an acid reagent under a heat treatment process, and then is sequentially mixed with a coupling agent and a copolymer, thereby optimizing the particle size and morphology of the rare earth permanent magnet powder, improving the particle dispersibility, and achieving the coating and modification of the surface of the permanent magnet powder. Then, combined with a composite process with a binder, not only does the resulting composite permanent magnet material have excellent magnetic properties and strong mechanical strength, but it also effectively reduces the shrinkage rate of the material when it is exposed to high temperatures for a long time.
[0064] (2) The composite permanent magnetic material provided by the present invention is prepared by a specific preparation method. The obtained composite permanent magnetic material has excellent magnetic properties, strong mechanical strength, and the shrinkage rate of the material is still low when it is exposed to high temperature for a long time. DETAILED DESCRIPTION
[0065] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0066] Example 1
[0067] This embodiment provides a method for preparing a composite permanent magnetic material, comprising the following steps:
[0068] (I) Sm2Fe with an average particle size of 20 μm 17 The N3 permanent magnet coarse material was ball milled with anhydrous ethanol as an auxiliary agent until the particle size D50 of the ball milled material was 3 μm. Then, the ball milled material was dried at 120°C under nitrogen protection. Then, the dried product was placed in a vibration mill for further crushing until the particle size D50 of the material was 1.8 μm, and the crushed Sm2Fe 17 N3 permanent magnet powder.
[0069] (II) The crushed Sm2Fe 17 The N3 permanent magnet powder was immersed in anhydrous ethanol and mixed evenly to obtain a mixed slurry, wherein the crushed Sm2Fe 17 The mass ratio of N3 permanent magnet powder to anhydrous ethanol is 1:1.5. Then, phosphoric acid with a concentration of 85wt% is added to the obtained mixed slurry. The amount of phosphoric acid added is 1:1.5 of the crushed Sm2Fe 17 The mixture is added with N3 permanent magnet powder accounting for 0.5wt% of the mass, and the mixing is continued. Then, the material after the phosphoric acid treatment is dried at 120° C. and heat-treated at 120° C. for 2 h to obtain a first mixed material.
[0070] (III) Soaking the first mixed material obtained in step (II) in anhydrous ethanol, wherein the mass ratio of the first mixed material to the anhydrous ethanol is 1:0.5, and then adding 0.5wt% of a silane coupling agent by mass based on the mass of the first mixed material. After mixing evenly, the mixed product is dried at 120°C to obtain a second mixed material.
[0071] (IV) The second mixed material obtained in step (III) is mixed with ethylene butyl acrylate copolymer, wherein the amount of ethylene butyl acrylate copolymer added is 0.5wt% of the mass of the second mixed material, and then the mixed product is placed in a nitrogen-protected internal mixer for 0.5h of internal mixing at a mixing temperature of 120°C to obtain a third mixed material.
[0072] (V) mixing the third mixed material obtained in step (IV) with nylon 12, wherein the mass ratio of the third mixed material to nylon 12 is 9:1; then, placing the mixed material into a twin-screw granulator for mixing and granulation to obtain a composite permanent magnet material.
[0073] Example 2
[0074] This embodiment provides a method for preparing a composite permanent magnetic material, comprising the following steps:
[0075] (I) Sm2Fe with an average particle size of 25 μm 17 The N3 permanent magnet coarse material was ball milled with anhydrous ethanol as an auxiliary agent until the particle size D50 of the ball milled material was 3.5 μm. Then, the ball milled material was dried at 110°C under nitrogen protection. Then, the dried product was placed in a vibration mill for further crushing until the particle size D50 of the material was 2 μm, and the crushed Sm2Fe 17 N3 permanent magnet powder.
[0076] (II) The crushed Sm2Fe 17 The N3 permanent magnet powder was immersed in anhydrous ethanol and mixed evenly to obtain a mixed slurry, wherein the crushed Sm2Fe 17The mass ratio of N3 permanent magnet powder to anhydrous ethanol is 1:1. Then, phosphoric acid with a concentration of 85wt% is added to the obtained mixed slurry. The amount of phosphoric acid added is 1:1. 17 The mixture is added with N3 permanent magnet powder accounting for 1.5wt% of the mass of the powder, and the mixing is continued. Then, the material after the phosphoric acid treatment is dried at 130° C. and heat-treated at 130° C. for 1 h to obtain a first mixed material.
[0077] (III) Soaking the first mixed material obtained in step (II) in anhydrous ethanol, wherein the mass ratio of the first mixed material to the anhydrous ethanol is 1:0.7, and then adding 0.8wt% of a silane coupling agent by mass based on the mass of the first mixed material. After mixing evenly, the mixed product is placed at 110° C. for drying to obtain a second mixed material.
[0078] (IV) The second mixed material obtained in step (III) is mixed with ethylene butyl acrylate copolymer, wherein the amount of ethylene butyl acrylate copolymer added is 1 wt% of the mass of the second mixed material, and then the mixed product is placed in a nitrogen-protected internal mixer for 2 hours at a mixing temperature of 110° C. to obtain a third mixed material.
[0079] (V) mixing the third mixed material obtained in step (IV) with nylon 12, wherein the mass ratio of the third mixed material to nylon 12 is 8:2; then, placing the mixed material into a twin-screw granulator for mixing and granulation to obtain a composite permanent magnet material.
[0080] Example 3
[0081] The difference between this embodiment and embodiment 1 is that in step (I), the dried product is subjected to vibration grinding until the particle size D50 of the material is 2.5 μm, that is, the crushed Sm2Fe 17 The particle size D50 of the N3 permanent magnet powder is 2.5 μm. The rest of the contents are the same as those in Example 1.
[0082] Example 4
[0083] The difference between this embodiment and embodiment 1 is that the amount of phosphoric acid added in step (II) is the amount of crushed Sm2Fe 17 The amount of N3 permanent magnet powder is 2 wt%. The rest of the contents are the same as those in Example 1.
[0084] Example 5
[0085] The difference between this embodiment and embodiment 1 is that the amount of the silane coupling agent added in step (III) is 1 wt% of the mass of the first mixed material. The rest of the contents are the same as those in embodiment 1.
[0086] Example 6
[0087] The difference between this embodiment and embodiment 1 is that the amount of ethylene butyl acrylate copolymerized in step (IV) is 2 wt% of the mass of the second mixture. The rest of the contents are the same as those in embodiment 1.
[0088] Example 7
[0089] The difference between this embodiment and embodiment 1 is that the mass ratio of the third mixed material to nylon 12 in step (V) is 9.1:0.9. The rest of the contents are the same as those in embodiment 1.
[0090] Example 8
[0091] The difference between this embodiment and embodiment 1 is that in step (I), the dried product is subjected to vibration grinding until the particle size D50 of the material is 1 μm, that is, the crushed Sm2Fe 17 The particle size D50 of the N3 permanent magnet powder is 1 μm. The rest of the contents are the same as those in Example 1.
[0092] Example 9
[0093] The difference between this embodiment and embodiment 1 is that the amount of phosphoric acid added in step (II) is the amount of crushed Sm2Fe 17 The amount of N3 permanent magnet powder is 0.1 wt%. The rest of the contents are the same as those in Example 1.
[0094] Example 10
[0095] The difference between this embodiment and embodiment 1 is that the amount of phosphoric acid added in step (II) is the amount of crushed Sm2Fe 17 The weight of N3 permanent magnet powder is 3 wt%. The rest of the contents are the same as those in Example 1.
[0096] Embodiment 11
[0097] The difference between this embodiment and embodiment 1 is that phosphoric acid in step (II) is replaced by acetic acid. The rest of the contents are the same as those in embodiment 1.
[0098] Example 12
[0099] The difference between this embodiment and embodiment 1 is that the temperature of the heat treatment in step (II) is 110° C. The rest of the contents are the same as those in embodiment 1.
[0100] Example 13
[0101] The difference between this embodiment and embodiment 1 is that the temperature of the heat treatment in step (II) is 150° C. The rest of the contents are the same as those in embodiment 1.
[0102] Embodiment 14
[0103] The difference between this embodiment and embodiment 1 is that the amount of the silane coupling agent added in step (III) is 0.1 wt% of the mass of the first mixed material. The rest of the contents are the same as those in embodiment 1.
[0104] Embodiment 15
[0105] The difference between this embodiment and embodiment 1 is that the amount of the silane coupling agent added in step (III) is 2 wt% of the mass of the first mixed material. The rest of the contents are the same as those in embodiment 1.
[0106] Example 16
[0107] The difference between this embodiment and embodiment 1 is that the amount of ethylene butyl acrylate copolymer added in step (IV) is 0.1 wt% of the mass of the second mixture. The rest of the contents are the same as those in embodiment 1.
[0108] Embodiment 17
[0109] The difference between this embodiment and embodiment 1 is that the amount of ethylene butyl acrylate copolymer added in step (IV) is 3 wt% of the mass of the second mixture. The rest of the contents are the same as those in embodiment 1.
[0110] Embodiment 18
[0111] The difference between this embodiment and embodiment 1 is that the mass ratio of the third mixed material to nylon 12 in step (V) is 7:3. The rest of the contents are the same as those in embodiment 1.
[0112] Embodiment 19
[0113] The difference between this embodiment and embodiment 1 is that nylon 12 in step (V) is replaced by nylon 6. The rest of the contents are the same as those in embodiment 1.
[0114] Embodiment 20
[0115] The difference between this embodiment and embodiment 1 is that the mixing process is omitted in step (IV). The rest of the contents are the same as those in embodiment 1.
[0116] Embodiment 21
[0117] The difference between this embodiment and embodiment 1 is that the preparation method of the composite permanent magnetic material provided in this embodiment omits step (I), that is, directly preparing Sm2Fe 17 The N3 permanent magnet coarse material is soaked in anhydrous ethanol, and a mixed slurry is formed under high-speed stirring, and then mixed with phosphoric acid. The rest of the contents are the same as in Example 1.
[0118] Comparative Example 1
[0119] This comparative example provides a method for preparing a composite permanent magnetic material, comprising the following steps:
[0120] S1. Sm2Fe with an average particle size of about 20 μm 17 The N3 permanent magnet coarse material was ball-milled in anhydrous ethanol until the particle size D50 of the ball-milled material was 2.3 μm. Then, the ball-milled material was dried at 120°C under nitrogen protection to obtain the pretreated Sm2Fe 17 N3 permanent magnet powder.
[0121] S2. The pretreated Sm2Fe 17 N3 permanent magnet powder was immersed in anhydrous ethanol, and Sm2Fe 17 The mass ratio of N3 permanent magnet powder to anhydrous ethanol is 1:0.5, and the mass of pretreated Sm2Fe 17 0.5wt% of silane coupling agent based on the mass of N3 permanent magnet powder is mixed evenly, and the mixed product is dried at 120° C. to obtain a mixed material.
[0122] S3. The mixture obtained in step S2 is mixed with nylon 12, wherein the mixing mass ratio of the mixture to nylon 12 is 9:1; then, the mixed product is placed in a twin-screw granulator for mixing and granulation to obtain a composite permanent magnet material.
[0123] Comparative Example 2
[0124] The difference between this comparative example and Example 1 is that the preparation method of the composite permanent magnetic material provided in this comparative example omits step (II), that is, directly crushing the Sm2Fe 17 The N3 permanent magnet powder is subjected to step (III), wherein the powder is immersed in anhydrous ethanol, and then a silane coupling agent is added and mixed. The rest of the contents are the same as those in Example 1.
[0125] Comparative Example 3
[0126] The difference between this comparative example and Example 1 is that the preparation method of the composite permanent magnetic material provided in this comparative example omits step (III), that is, directly mixing the first mixed material obtained in step (II) with the ethylene butyl acrylate copolymer. The rest of the contents are the same as Example 1.
[0127] Comparative Example 4
[0128] The difference between this comparative example and Example 1 is that the preparation method of the composite permanent magnetic material provided in this comparative example omits step (IV), that is, the second mixed material obtained in step (III) is directly mixed with nylon 12. The rest of the contents are the same as Example 1.
[0129] The performance of the composite permanent magnetic material obtained by the preparation method provided in the above Examples 1-21 and Comparative Examples 1-4 was tested, and the specific testing process was as follows:
[0130] The composite permanent magnetic materials prepared in Examples 1-21 and Comparative Examples 1-4 were injection molded at a temperature of 270°C, a pressure of 300 MPa, and a holding time of 5 seconds to obtain a magnetic ring with an inner diameter of 30 mm, an outer diameter of 35 mm, and a height of 10 mm. The magnetic properties of the magnetic ring were tested using a BH tester, and the tensile strength and bending strength were tested using a comprehensive mechanical tester. The obtained magnetic ring was placed at 120°C for 24 hours, and the shrinkage rate of the magnetic ring was calculated by comparing the change in the inner diameter of the magnetic ring before and after the insulation. The calculation formula is: (inner diameter of the magnetic ring before insulation - inner diameter of the magnetic ring after insulation) / inner diameter of the magnetic ring before insulation. The test results are shown in Table 1.
[0131] Table 1
[0132]
[0133]
[0134] The test results show that:
[0135] (1) It can be seen from Examples 1 to 7 that the composite permanent magnetic material obtained by the preparation method of the present invention has high magnetic properties and high mechanical strength. At the same time, the shrinkage rate of the material is low when it is exposed to high temperatures for a long time. The comprehensive performance of the composite permanent magnetic material obtained is excellent.
[0136] (2) By comparing Example 1 with Example 8, it can be seen that in step (I) of the present invention, if the particle size D50 of the rare earth permanent magnet powder after crushing is too small, the magnetic properties of the composite permanent magnet material will be reduced, the mechanical strength will be poor, and the shrinkage rate will increase.
[0137] (3) By comparing Example 1 with Examples 9-10, it can be seen that if the amount of the acid reagent added is too low, the magnetic properties and mechanical strength of the composite permanent magnetic material will deteriorate, and the shrinkage rate of the material will increase; if the amount of the acid reagent added is too high, the magnetic properties of the composite permanent magnetic material will be greatly reduced, and the mechanical strength will deteriorate.
[0138] (4) By comparing Example 1 with Example 11, it can be seen that if phosphoric acid is replaced by acetic acid in the present invention, the magnetic properties and mechanical properties of the obtained composite permanent magnetic material will deteriorate, and the shrinkage rate of the material will increase.
[0139] (5) By comparing Example 1 with Examples 12-13, it can be seen that if the heat treatment temperature of the present invention is too low, the magnetic properties and mechanical properties of the obtained composite permanent magnet material will deteriorate, and the shrinkage rate will increase; if the heat treatment temperature is too high, although the magnetic properties of the finally prepared composite permanent magnet material can be reduced to a low degree, the excessively high temperature will increase energy consumption and affect the mechanical strength and shrinkage rate of the obtained material.
[0140] (6) By comparing Example 1 with Examples 14-15, it can be seen that if the amount of coupling agent added in the present invention is too small, the compatibility of the materials cannot be improved, thereby causing the reaction effect between the materials and the subsequent copolymer to deteriorate, affecting the comprehensive performance of the final composite permanent magnetic material; if the amount of coupling agent added is too large, the non-magnetic phase in the composite permanent magnetic material will increase and the magnetic properties will decrease.
[0141] (7) By comparing Example 1 with Examples 16-17, it can be seen that if the amount of the copolymer added in the present invention is too small, the second mixed material cannot be effectively coated, so that the rare earth permanent magnetic powder inside the material is easily oxidized, affecting the magnetic properties of the obtained composite permanent magnetic material, and affecting the composite effect of the material and the binder, thereby increasing the shrinkage rate of the final composite permanent magnetic material; if the amount of the copolymer added is too much, its proportion in the composite permanent magnetic material is too high, resulting in a decrease in the magnetic properties of the material.
[0142] (8) By comparing Example 1 with Example 18, it can be seen that in the present invention, if the mass ratio of the third mixed material to the binder is too low and the amount of binder added is too much, the magnetic properties of the resulting composite permanent magnet material will be significantly reduced, and the shrinkage rate of the material will be greatly increased.
[0143] (9) By comparing Example 1 with Example 19, it can be seen that if nylon 12 is replaced by nylon 6 in the present invention, the magnetic properties of the composite permanent magnet material finally prepared will be greatly reduced.
[0144] (10) By comparing Example 1 with Example 20, it can be seen that if the mixing process of step (IV) is omitted in the present invention, the material will be significantly agglomerated, affecting the subsequent composite effect with the binder, thereby causing the overall performance of the obtained composite permanent magnet material to deteriorate.
[0145] (11) By comparing Example 1 with Example 21, it can be seen that if the ball milling and vibration milling processes in step (I) of the present invention are omitted, the magnetic properties of the resulting composite permanent magnet material will become extremely poor and almost non-magnetic.
[0146] (12) By comparing Example 1 with Comparative Example 1, it can be seen that the preparation method of the composite permanent magnetic material provided by the present invention is as follows: if the Sm2Fe17 After the N3 permanent magnet powder is mixed with the coupling agent, it directly reacts with the binder, resulting in a significant decrease in the mechanical strength of the resulting composite permanent magnet material, and a significant increase in the shrinkage rate of the material when it is exposed to high temperature for a long time.
[0147] (13) By comparing Example 1 with Comparative Examples 2-4, it can be seen that if the present invention omits the reaction with phosphoric acid in step (II) and the subsequent heat treatment process, or omits the mixing process with the coupling agent in step (III), or omits the mixing process with the ethylene butyl acrylate copolymer in step (IV), the magnetic properties and mechanical strength of the obtained composite permanent magnet material will be significantly deteriorated, the shrinkage rate of the material will be significantly increased when it is exposed to high temperatures for a long time, and the overall performance of the material will be poor.
[0148] In summary, in the preparation method of the present invention, the rare earth permanent magnet powder reacts with the acid reagent under a heat treatment process, and then is sequentially mixed with the coupling agent and the copolymer, thereby optimizing the particle size and morphology of the rare earth permanent magnet powder, improving the particle dispersibility, and realizing the coating and modification of the surface of the permanent magnet powder. Then, combined with the composite process with the binder, not only the obtained composite permanent magnet material has excellent magnetic properties and strong mechanical strength, but also the shrinkage rate of the material under high temperature and long-term working is effectively reduced, thereby obtaining a composite permanent magnet material with excellent comprehensive performance.
[0149] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite permanent magnetic material, characterized in that: The preparation method comprises the following steps: (1) performing a first mixing of rare earth permanent magnet powder, an acid reagent and a first solvent, and then performing a heat treatment to obtain a first mixed material; (2) performing a second mixing of the first mixed material, the coupling agent and the second solvent to obtain a second mixed material; (3) performing a third mixing of the second mixed material and the copolymer to obtain a third mixed material; (4) The third mixed material is mixed with a binder for a fourth time to obtain the composite permanent magnetic material.
2. The preparation method according to claim 1, characterized in that: The rare earth permanent magnet powder in step (1) comprises samarium iron nitrogen magnetic powder; Preferably, the particle size D50 of the rare earth permanent magnet powder in step (1) is 1.8-2.5 μm; Preferably, the rare earth permanent magnet powder in step (1) is prepared by ball milling and then vibrating rare earth permanent magnet coarse material; Preferably, the average particle size of the rare earth permanent magnet coarse material is 15-25 μm; Preferably, the ball milling aid includes ethanol.
3. The preparation method according to claim 1 or 2, characterized in that: The acid reagent in step (1) includes phosphoric acid; Preferably, in step (1), the amount of the acid reagent added is 0.5-2wt% of the mass of the rare earth permanent magnet powder; Preferably, in step (1), the mass ratio of the rare earth permanent magnet powder to the first solvent is 1:(1-2).
4. The preparation method according to any one of claims 1 to 3, characterized in that The specific process of the first mixing in step (1) includes: mixing the rare earth permanent magnet powder with a first solvent to form a mixed slurry, and then mixing the mixed slurry with the acid reagent; Preferably, after the first mixing in step (1), the mixed product obtained by the first mixing is also dried; Preferably, the drying temperature is 120-130°C.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the heat treatment in step (1) is 120-130°C; Preferably, the heat treatment time in step (1) is 1-3 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (2), the coupling agent is added in an amount of 0.5-1.0 wt% of the mass of the first mixed material; Preferably, in step (2), the mass ratio of the first mixed material to the second solvent is 1:(0.3-0.8); Preferably, the second mixed product in step (2) is also dried; Preferably, the drying temperature is 110-130°C.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (3), the amount of the copolymer added is 0.5-2.0wt% of the mass of the second mixed material; Preferably, the copolymer in step (3) comprises ethylene butyl acrylate copolymer; Preferably, the product after the third mixing in step (3) is further subjected to banburying to obtain the third mixed material; Preferably, the banburying is carried out in nitrogen and / or inert gas; Preferably, the temperature of the banburying is 110-130°C; Preferably, the kneading time is 0.5-2h.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The binder in step (4) comprises nylon 12; Preferably, in step (4), the mass ratio of the third mixed material to the binder is (8-9.5):(0.5-2); Preferably, after the fourth mixing in step (4), the mixed material is further kneaded and granulated.
9. A composite permanent magnetic material, characterized in that: The composite permanent magnetic material is prepared by the preparation method described in any one of claims 1 to 8.
10. An application of the composite permanent magnetic material according to claim 9, characterized in that: The composite permanent magnetic material is applied in the fields of computers, automobiles, household products, aerospace, medical equipment or instruments.
Citation Information
Patent Citations
Preparation method of high-performance modified SmFeN magnetic powder, and preparation method of high-performance modified permanent magnet
CN112331472A